"Evaluación sensorial de una bebida alcohólica a base de maíz morado (Zea mays L.) con adición de aguardiente rectificado" - Alcívar Martínez, Jean Stalin (2020)
Purple corn (Zea mays L.) is characterized by its purple hue due to its large amount of anthocyanins, which is a food rich in antioxidants and of great nutritional value. The research on obtaining the alcoholic beverage was carried out with the extraction of spice juices and pineapple peel plus purple corn for 60 minutes, plus a standardized filtering with citric acid and sugar in order to later store it, and then perform the Mix with rectified liquor and reach concentrations of 3,6,9,12,15 and 18 ° GL until obtaining the final product within the previous ones of the State Technical University of Quevedo, extension of the experimental farm La Maria (dairy and sausage laboratory) . Where in the investigation a completely randomized experimental design was formulated. And thus standardize the process, using purple corn drink and adding rectified alcohol 3,6,9,12,15 and 18 ° A, pH was determined where the highest average was for T5 with 4.57 and the lowest for T1 with 4.38 the acidity was 0.20 T4 and 0.333 for T2, T5 and T6, the soluble solids 5.76 brix T1 10.80 for T6, density 1.023 T6 and 1.038 T1 and the viscosity of 1.151 T1 and 1.691 T6; The organoleptic evaluation was carried out to identify the best sensory characteristics and greater acceptance for the consumer. Keywords: Aguardiente, purple corn, sensory, physical characteristics, chemical.